A hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst and preparation method thereof
By developing an electrocatalyst for oxygen reduction reaction of hollow multi-stage porous carbon nanocages, the active position density of existing carbon-based non-metallic ORR electrocatalysts in acidic media is solved by using the synergistic catalytic effect of graphene and zeolite imidazole metal covalent organic frameworks. The problems of low and poor quality transmission performance achieve catalytic performance and stability similar to Pt/C.
Patent Information
- Application Number
- CN202110692825.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-06-22
AI Technical Summary
The existing carbon-based non-metallic ORR electrocatalysts have low active position density and poor mass transfer performance in acidic media, which is difficult to meet the needs of practical applications.
Develop an electrocatalyst for oxygen reduction reaction of hollow multi-stage porous carbon nanocages, a hollow multi-stage porous carbon nanocage structure formed by hybridization of non-metal heteroatom-doped graphene nanosheets and covalent organic frameworks of zeolite imidazoles. The synergistic catalytic effect between different components is used to improve catalytic activity and substance transportability.
It exhibits ORR catalytic performance similar to commercial Pt/C in acidic media, with the oxygen reduction half-wave potential up to 0.79V, the Taffir slope is small and the stability is good, and it is suitable for cathode catalysts for hydrogen fuel cells.
Smart Images

Figure CN115513478B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanomaterials, and in particular relates to a hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst and a preparation method thereof. Background Art
[0002] Hydrogen fuel cell technology based on electrocatalysis is an important measure to solve the energy crisis and environmental pollution. In hydrogen fuel cell systems, efficient oxygen reduction reaction (ORR) at low overpotential is crucial to improving energy utilization. At present, Pt-based materials are still used commercially as cathode catalysts for hydrogen fuel cells, but their high cost, low earth reserves, poor tolerance and easy poisoning seriously restrict their large-scale commercialization. Transition metal catalysts are considered to be effective substitutes for Pt cathodes in fuel cells due to their abundant resources and low cost. However, the inevitable metal corrosion, dissolution or poisoning during the reaction makes it difficult for most metal catalysts to maintain long-term stable catalytic activity in acidic media. In order to overcome the corrosion and leaching problems of metals in acidic environments, metal-free catalysts have become the best choice for improving durability. Among them, carbon-based metal-free catalysts have shown broad application prospects in the field of energy catalysis due to their high conductivity, strong tolerance and easy modification. However, the poor ORR catalytic activity and material transport properties of metal-free carbon materials in acidic media make it difficult to meet the needs of practical applications.
[0003] Ideal electrode materials should have high electrical conductivity, large specific surface area and pathways that are conducive to material / electron transport. Regulating the micro-nanostructure to increase the specific surface area of the material, expose the catalytic active centers, and shorten the ion diffusion distance is considered to be an effective means to improve the catalytic performance of electrode materials. Generally, discrete nanocarbons are prone to aggregation / re-accumulation during electrode preparation, resulting in low porosity and poor mass transfer performance, which greatly reduces the catalytic efficiency of energy. Summary of the invention
[0004] In order to solve the problems of low active site density and poor mass transfer performance of existing carbon-based non-metallic ORR electrocatalysts in acidic media, the present invention develops a hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst and its preparation method. This new catalyst can be used as a non-metallic cathode material, thereby greatly reducing the commercial cost of hydrogen fuel cells, has the potential value of large-scale commercial application, and can effectively promote the rapid development of the new energy economy.
[0005] In the first aspect, the present invention provides a hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst (also referred to as a "carbon-based non-metallic oxygen reduction reaction catalyst"). The electrocatalyst has a hollow multi-level porous carbon nanocage structure formed by hybridization of non-metallic heteroatom-doped graphene nanosheets and a zeolite imidazole metal covalent organic framework with a surface modified positive charge; the non-metallic heteroatom-doped graphene nanosheets and the zeolite imidazole metal covalent organic framework are in close contact to form a nano heterojunction.
[0006] The non-metallic heteroatom doped graphene nanosheets account for 25-50% by mass of the hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst, preferably 35-50%. This helps the graphene to be evenly coated on the surface of the zeolite imidazole metal covalent organic framework, avoiding the agglomeration of excess graphene, which makes it difficult for the graphene nanosheets to be in close contact with the zeolite imidazole metal covalent organic framework to produce a heterogeneous structure. In some technical solutions, the non-metallic heteroatom includes but is not limited to at least one of boron, nitrogen, sulfur, phosphorus and fluorine.
[0007] Zeolitic imidazolate metal covalent organic framework is a type of zeolitic imidazolate framework material (Zeolitic imidazolate frameworks, ZIFs) with a silicon-aluminum molecular sieve structure. Preferably, the zeolitic imidazolate metal covalent organic framework includes but is not limited to ZIF-8, ZIF-20, ZIF-90, ZIF-4, ZIF-7, etc. Preferably, the zeolitic imidazolate metal covalent organic framework is ZIF-8 (also known as "2-methylimidazole zinc salt").
[0008] In the electrocatalyst of the present invention, functionalized non-metallic heteroatom-doped graphene nanosheets and zeolite imidazole metal covalent organic frameworks (such as ZIF-8) interact to produce an effective synergistic catalytic effect. The close interfacial interaction of different components can produce a large number of electron transfer pathways, while inducing electronic coupling at the interface, accelerating the electron transfer process at the interface, and optimizing the energy adsorption state of the intermediate, which is conducive to improving the ORR catalytic activity of carbon-based non-metallic materials. For example, zeolite imidazole metal covalent organic frameworks (ZIF-8) are doped with nitrogen atoms as heteroatoms, and the heteroatoms in non-metallic doped graphene can be the same or heterogeneous atoms, so that there needs to be a charge difference between the two doped substances, thereby generating electron transfer between interfaces.
[0009] Preferably, the mass percentage of heteroatoms in the non-metallic heteroatom-doped graphene nanosheets is 3 to 10%, preferably 4.5 to 10%. In particular, the mass percentage of heteroatoms in the graphene nanosheets is higher than the mass percentage of heteroatoms in the product obtained after pyrolysis of the zeolite imidazole metal covalent organic framework. In the catalyst designed by the present invention, the mass percentage of heteroatoms in the graphene nanosheets is preferably higher than the mass percentage of heteroatoms in the product obtained after pyrolysis of the zeolite imidazole metal covalent organic framework, so that an electron transfer process from graphene to the zeolite imidazole metal covalent organic framework occurs, which is conducive to the generation of electron transfer pathways between interfaces. The path and direction of electron transfer are determined based on the difference in interfacial charge induced by different amounts or different types of heteroatoms. The difference in the above heteroatom mass percentages is preferably between 2% and 6%.
[0010] Preferably, the specific surface area of the hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst is 300 to 1000 m 2 / g.
[0011] Preferably, the size of the carbon nanocage is 100-300 nm. Carbon-based nanocages have large internal cavities and sub-nanometer mass transfer channels, which are conducive to the material to produce a larger specific surface area, expose more catalytic active sites, and promote the exchange and transfer of substances in electrochemical reactions.
[0012] Preferably, the electrocatalyst has a hierarchical porous structure in which micropores, mesopores and macropores are interconnected and coexist. The hierarchical porous structure has interconnected hierarchical pores, which is beneficial to improving mass transfer efficiency. The hollow multi-level porous carbon skeleton can also increase the specific surface area of the material, expose more catalytic active centers, and accelerate the process of electron transfer and ion migration / diffusion. The pore size range is 0.6 to 100 nm. Preferably, the pore size of the micropores is 0.1 to 1.5 nm, the pore size of the mesopores is 4 to 100 nm, and the pore size of the macropores is 100 to 150 nm.
[0013] The electrocatalyst of the present invention has high catalytic activity and material transport properties, and exhibits ORR catalytic performance comparable to that of commercial Pt / C (20wt%) in acidic medium. 1 / 2 ) can reach 0.79V, and has a small Tafel slope (73mV dec -1 ), good stability and resistance to methanol poisoning. 2 / O 2 In fuel cell tests, the material can be used as a cathode catalyst with a maximum power density of 431 mW cm -1, and has good operational stability. In addition, the catalyst of the present invention is a non-metal-doped carbon nanocage heterostructure catalyst without metal loading, and its ORR catalytic activity in acidic medium is comparable to that of commercial Pt / C, and has good catalytic stability.
[0014] In a second aspect, the present invention provides a method for preparing a hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst as described in any of the above items. The preparation method uses heteroatom-doped graphene and zeolite imidazole metal covalent organic framework cubes with positive charges on the surface as building blocks, forms a carbon nano hybrid material through non-covalent interactions between the two, and uses small molecule hot air flow generated by acetate decomposition to swell the micropores in the zeolite imidazole metal covalent organic framework, and finally forms a multi-level porous structure with an internal cavity.
[0015] Preferably, the preparation method comprises the following steps:
[0016] 1) Synthesize non-metallic heteroatom-doped graphene nanosheets using a hydrothermal method;
[0017] 2) Preparation of zeolitic imidazole metal covalent organic framework nanocubes with surface modification of positive charges;
[0018] 3) electrostatically self-assembling the non-metallic heteroatom-doped graphene nanosheets and the surface-modified positively charged zeolite imidazole metal covalent organic framework nanocubes to obtain a non-metallic heteroatom-doped graphene / zeolite imidazole metal covalent organic framework hybrid material;
[0019] 4) Placing the non-metallic heteroatom doped graphene / zeolite imidazole metal covalent organic framework hybrid material on the surface of copper foam with acetate groups, and pyrolyzing it at high temperature in an inert atmosphere to obtain the hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst.
[0020] The preparation method of the present invention is simple and easy to operate, and can omit the cost pressure brought by the complicated preparation process and post-processing of the template method for large-scale production, and can prevent the core size and morphology from being difficult to accurately control due to the violent inward contraction of the carbon skeleton during the carbonization process. The oxygen reduction reaction electrocatalyst formed by the preparation method is mainly composed of non-metal-doped hybrid carbon materials, and functionalized graphene is tightly coated on the surface of the zeolite imidazole metal covalent organic framework cube, forming a hollow hierarchical porous nanocage structure during the controlled pyrolysis process. This structure is conducive to the generation of a large active surface area and a fast material transmission pathway. Through the synergistic catalysis between different components, the non-metal catalyst exhibits an ORR catalytic activity equivalent to that of commercial Pt / C (20wt%) in an acidic medium, which greatly reduces the application cost of the cathode catalyst and has a high economic benefit.
[0021] Preferably, in step 1), synthesizing non-metallic heteroatom-doped graphene nanosheets by hydrothermal method comprises: ultrasonically dispersing a heteroatom dopant into an aqueous dispersion of graphene oxide, and obtaining heteroatom-doped graphene nanosheets by hydrothermal reaction; preferably, the temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 12-24 h; more preferably, the mass ratio of the heteroatom dopant to the graphene oxide is (1-5): (0.1-0.5); further preferably, the heteroatom dopant is at least one of boric acid, melamine, urea, dibenzyl disulfide, triphenyl phosphine, thiourea and ammonium fluoride.
[0022] Preferably, in step 2), preparing the surface-modified positively charged zeolite imidazole metal covalent organic framework nanocubes comprises: uniformly mixing 2-methylimidazole, zinc nitrate hexahydrate and a cationic surfactant, stirring and standing to obtain the surface-modified positively charged zeolite imidazole metal covalent organic framework nanocubes; preferably, the mass ratio of the 2-methylimidazole, zinc nitrate hexahydrate and the cationic surfactant is (1-10): (0.1-1): (0.01-0.06); more preferably, the cationic surfactant is at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and hexadecyldimethylbenzylammonium chloride; further preferably, the standing time is 5-24h.
[0023] Preferably, in step 4), the pyrolysis temperature is 700-1000° C. and the pyrolysis time is 3-5 h.
[0024] Beneficial effects:
[0025] The electrocatalyst has a hollow multi-level pore nanostructure, which can buffer the volume expansion and contraction changes of the active components during the cycle, greatly improving the utilization rate of the active sites;
[0026] The electrocatalyst utilizes the synergistic catalytic effect between different components, which is beneficial to improving the ORR catalytic performance of the non-metallic catalyst in an acidic medium;
[0027] The heterojunction structure of the electrocatalyst promotes a synergistic catalytic effect between the components;
[0028] The preparation method of the electrocatalyst develops a new means of in-situ generation of hollow multi-level pore nanocages by a small molecule thermal gas flow method, thereby improving the process complexity of preparing nanocage materials by a hard template method. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The STEM image (scanning transmission electron microscope) of the NC / G@HNCs material prepared in Example 1 of the present invention is shown;
[0030] Figure 2The TEM-HADDF (field emission transmission electron microscopy) image of the NC / G@HNCs material prepared in Example 1 of the present invention is shown;
[0031] Figure 3 The cyclic voltammetry curves of NC / G@HNCs prepared in Example 1 of the present invention and commercial Pt / C (20 wt %) are shown;
[0032] Figure 4 A comparison chart of the ORR curves of the NC / G@HNCs material prepared in Example 1 of the present invention, NCs, NC / Gs and commercial Pt / C (20 wt%) is shown;
[0033] Figure 5 A comparison of the Tafel slopes of the NC / G@HNCs material prepared in Example 1 of the present invention, NCs, NC / Gs, and commercial Pt / C (20 wt%) is shown;
[0034] Figure 6 A stability test comparison diagram of the NC / G@HNCs material prepared in Example 1 of the present invention and commercial Pt / C (20wt%) is shown;
[0035] Figure 7 The results show that the NC / G@HNCs material prepared in Example 1 of the present invention is similar to NCs, NC / Gs and commercial Pt / C (20 wt%) in H 2 / O 2 Comparison of power density curves in fuel cell test systems;
[0036] Figure 8 It shows that the NC / G@HNCs material prepared in Example 1 of the present invention has 2 / O 2 Stability graphs in fuel cell test systems;
[0037] Fig. 9 The ORR performance comparison of HNCs, N-CG, NC / G@HNCs and Pt / C materials is shown;
[0038] Fig.10 The STEM image of the N-CG material without forming a graphene-coated ZIF-8 structure prepared in Comparative Example 2 of the present invention is shown;
[0039] Fig.11 The zeta potential values of non-metallic heteroatom-doped graphene nanosheets (NG), positively charged zeolitic imidazolate metal covalent organic frameworks (ZIF-8), and their composites (ZIF-8 / NG) are shown. DETAILED DESCRIPTION
[0040] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. In the absence of special instructions, each percentage content refers to the percentage content by mass.
[0041] The hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst of the present invention is a hollow multi-level porous carbon nano cage catalyst formed by hybridization of non-metallic heteroatom doped graphene and zeolite imidazole metal covalent organic framework. The heteroatom doped graphene in the electrocatalyst is tightly coated on the surface of the zeolite imidazole metal covalent organic framework cube to form a heterojunction structure. The heterojunction structure is conducive to enhancing the electron transfer at the interface, generating abundant interface catalytic active sites, and synergistically promoting O 2 The adsorption and reduction kinetics of ORR can be improved, thereby enhancing the ORR catalytic activity and electrode current density.
[0042] The nano cage of the present invention does not contain metal elements. The metal elements in the zeolite imidazole metal covalent organic framework, such as zinc, are completely removed during the high-temperature pyrolysis process. Moreover, the nano cage of the present invention has a cubic structure and a large internal cavity, which provides the required channel for material transport. The outer wall of the carbon nano cage contains a multi-level pore structure (a hierarchical porous structure in which micropores, mesopores and macropores are connected and coexist).
[0043] The zeolite imidazole metal covalent organic framework includes but is not limited to ZIF-8, ZIF-20, ZIF-90, ZIF-4, ZIF-7, etc. Preferably, the zeolite imidazole metal covalent organic framework is ZIF-8 (also referred to as "2-methylimidazole zinc salt"). Through the close-range interfacial electronic coupling and rapid electron transfer between different components of heteroatom-doped graphene and zeolite imidazole metal covalent organic framework, new adjustable interfacial catalytic active sites are generated, thereby improving the intrinsic catalytic activity of the material. The specific reason is that due to the difference in heteroatom doping amount and electronegativity between different components, there will be a difference in charge between different components, thereby causing intermolecular electron transfer and generating an electron coupling effect at the interface; wherein the doping of unequal amounts and different kinds of heteroatoms is the main reason for inducing inter-interfacial electron transfer and coupling.
[0044] At present, the controllable synthesis of a non-metallic hollow multi-level porous carbon nanocage as an efficient and durable cathode ORR electrocatalyst still faces great challenges. The preparation method of the non-metallic doped hollow multi-level porous carbon nanocage catalyst of the present invention uses heteroatom-doped graphene and zeolite imidazole metal covalent organic framework cubes with positive charges on the surface as building blocks, forms a carbon nano hybrid material through non-covalent interaction between the two, and uses the small molecule hot air flow generated by the decomposition of acetate to swell the micropores in the zeolite imidazole metal covalent organic framework, and finally forms a multi-level porous structure with an internal cavity.
[0045] The following is an exemplary description of the preparation method of the novel non-metallic hollow multi-level porous carbon nanocage oxygen reduction reaction (ORR) electrocatalyst of the present invention.
[0046] Non-metallic heteroatom-doped graphene nanosheets are synthesized by hydrothermal method. A certain amount of heteroatom dopant is weighed and ultrasonically dispersed into a certain concentration of graphene oxide aqueous dispersion, and graphene nanosheets doped with different heteroatoms are obtained by hydrothermal method. By adding different types of heteroatom dopant, the specified heteroatom can be doped into the carbon skeleton of graphene by hydrothermal method. The heteroatom dopant includes but is not limited to at least one of boric acid (B), melamine (N), urea (N), dibenzyl disulfide (S), triphenylphosphine (P), thiourea (S, N) and ammonium fluoride (N, F). The input ratio of dopant and graphene oxide, hydrothermal temperature and reaction time can be optimized according to actual conditions. For example, the concentration of the aqueous dispersion of graphene oxide can be 0.001-0.01 g / mL; the input mass ratio of heteroatom dopant to graphene oxide can be (1-5): (0.1-0.5); the hydrothermal temperature can be 160-200°C, the reaction time can be 12-24 hours; the pressure of the hydrothermal reaction can be 2-20 MPa. Through Zeta potential test ( Fig.11 ) proved that non-metallic heteroatom-doped graphene is negatively charged.
[0047] In one example, a certain amount of urea was dissolved in a certain concentration of graphene oxide aqueous dispersion, and then heated to 200° C. in a 40-100 ml polytetrafluoroethylene reactor for 18 h to obtain N-doped graphene nanosheets (named NG).
[0048] The invention discloses a zeolitic imidazole metal covalent organic framework nanocube with surface modification positive charge, such as ZIF-8 nanocube. In particular, 2-methylimidazole, zinc nitrate hexahydrate and cationic surfactant are used as raw materials, and ZIF-8 nanocube with surface positive charge is prepared by stirring at room temperature.
[0049] A certain amount of 2-methylimidazole, zinc nitrate hexahydrate and a cationic surfactant are uniformly mixed, stirred and allowed to stand to obtain a surface-modified positively charged ZIF-8 nanocube. The input mass ratio of 2-methylimidazole, zinc nitrate hexahydrate and cationic surfactant can be (1-10): (0.1-1): (0.01-0.06). The standing time can be 5-24 hours. By adjusting the ratio of the added precursors (2-methylimidazole, zinc nitrate hexahydrate and cationic surfactant) and the standing time, ZIF-8 nanocubes with different sizes and dimensions are prepared. Preferably, the size of the ZIF-8 nanocube is 100-250nm.
[0050] Then, the graphene is tightly coated on the surface of the zeolitic imidazole metal covalent organic framework by electrostatic self-assembly to form a graphene / zeolitic imidazole metal covalent organic framework hybrid material. That is, the heteroatom-doped graphene nanosheets and the zeolitic imidazole metal covalent organic framework nanocubes with positively charged surfaces are electrostatically self-assembled.
[0051] For example, heteroatom-doped graphene nanosheets and ZIF-8 nanocubes are uniformly mixed at a mass ratio of 1:1 to 1:3 and stirred for 20 minutes before separation to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The separation method can be centrifugal. For example, centrifugal washing is performed 3 times, each time for 5 minutes. Heteroatom-doped graphene is tightly coated on the surface of the cube to form an intermolecular nano-heterogeneous structure.
[0052] The heteroatom-doped graphene / zeolite imidazole metal covalent organic framework hybrid material is attached to the surface of copper foam with acetate ions and heat-treated under an inert atmosphere. The small molecular gas flow generated by the high-temperature thermal decomposition of acetate ions swells the microporous structure in the zeolite imidazole metal covalent organic framework, and the product after thermal decomposition becomes a carbon skeleton, which accelerates the dissociation of metal ions and the formation of a multi-level pore structure.
[0053] In some embodiments, the copper foam is immersed in an acetate solution for 10-24 hours, and after drying, the heteroatom-doped graphene / zeolite imidazole metal covalent organic framework nanohybrid material is attached to the surface of the copper foam with acetate groups and then heat-treated to obtain a non-metallic hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst. The types of acetate include but are not limited to one of sodium acetate, potassium acetate, iron acetate, cobalt acetate, nickel acetate, copper acetate, iron acetate, manganese acetate and zinc acetate. The growth and change process of the nanostructure can be controlled by changing the type, concentration and heat treatment temperature of the acetate, thereby obtaining a hollow multi-level porous carbon nano cage with different sizes and morphologies. The concentration of the acetate solution can be 0.5-3 mol / L. The heat treatment can be carried out in a tubular furnace. For example, after argon is introduced into the tubular furnace for 30-60 minutes, it is heated to the heat treatment temperature at a heating rate of 2-5°C / minute. The heat treatment temperature can be 700-1000°C, and the time can be 3-5h.
[0054] In one example, for example, a nitrogen-doped graphene / ZIF-8 hybrid material can be attached to a copper foam surface with sodium acetate, and placed in a tube furnace, heated to 900°C at a heating rate of 5°C / min and kept warm for 4 hours in a nitrogen atmosphere to obtain a nitrogen-doped hollow multi-level porous carbon nanocage catalyst. In this process, the acetate is thermally decomposed under an inert atmosphere to produce a small molecule gas flow to swell the micropores in the hybrid material, accelerate the dissociation of metal ions (zinc ions) in the organic framework and the reconstruction of the pore structure, and finally obtain a heteroatom-doped hollow multi-level porous carbon nanocage electrocatalyst.
[0055] The hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst of the present invention is 0.5MH 2 SO 4 The half-wave potential in solution is comparable to that of commercial Pt / C. At the same time, it also has a limiting current density, Tafel slope and catalytic stability that are superior to those of Pt / C catalysts. 2 / O 2 In the fuel cell test, it has a peak power density close to that of Pt / C and good battery stability. Moreover, the preparation method of the hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst is simple and easy to operate. Using cheap carbon-based non-metallic catalysts as electrode materials to replace Pt cathodes is of great significance for promoting the large-scale commercialization of hydrogen fuel cells.
[0056] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0057] Example 1
[0058] First, prepare heteroatom-doped graphene nanosheets. Taking nitrogen-doped graphene as an example, first weigh 1.5g of urea and disperse it in 20mL of graphene oxide dispersion (2mg / mL), ultrasonicate for 30min to completely dissolve the urea, then place the dispersion after dissolving urea in a polytetrafluoroethylene reactor, react at 160℃ for 15h, filter, wash and dry to obtain nitrogen-doped graphene nanosheets (NG). Dissolve 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB in 50mL of deionized water, stir and dissolve, let stand for 5h, centrifuge, wash and dry to obtain ZIF-8 nanocubes. Mix NG and ZIF-8 uniformly in a mass ratio of 1:1, stir for 20min, centrifuge and wash 3 times, 5min each time, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h. After drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam and placed in a tubular furnace. After argon gas was introduced for 30 min, it was heated to 800 °C at a heating rate of 5 °C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs).
[0059] like Figure 1 and Figure 2 As shown, the nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst has a hollow nanocage size of about 200 nm and contains three pore size distributions of micropores, mesopores and macropores.
[0060] The electrocatalytic oxygen reduction reaction performance of the NC / G@HNCs material prepared in Example 1 was tested using a Shanghai Chenhua 760E electrochemical workstation and an American PINE rotating disk electrode. The Ag / AgCl electrode and the carbon rod were used as the reference electrode and the counter electrode, respectively. 2 SO 4 The working electrode is Al 2 O 3 The powder was polished, and then the electrode was ultrasonically cleaned with deionized water and ethanol respectively. Drying under infrared lamp, 10mg of the above-prepared NC / G@HNCs hybrid material was added to a mixture of 30uL Nafion and 1.25mL ethanol for ultrasonic treatment to obtain a uniformly dispersed suspension. 10uL of the suspension was added to the polished glassy carbon electrode, and the solvent was evaporated and removed under infrared lamp irradiation to obtain a working electrode with a NC / G@HNCs electrocatalyst film coated on the surface of the glassy carbon electrode. High-purity nitrogen or oxygen was introduced for 15 minutes before the test to saturate the gas in the electrolyte, and scanning activation was performed at a rate of 50mV / s at room temperature.
[0061] The oxygen reduction performance of the NC / G@HNCs material prepared in Example 1 was tested. Figure 3 As shown in Figure 2, the peak potential and half-wave potential of NC / G@HNCs are 0.78 V and 0.79 V, respectively, which are comparable to those of Pt / C catalysts. At the same time, it also has a limiting current density ( Figure 4 )、Tafel slope( Figure 5 ) and good catalytic stability ( Figure 6 ). 2 / O 2 In the fuel cell test, the NC / G@HNCs catalyst (431 mW cm -2 ) has a value close to that of Pt / C (580 mW cm -2 )'s peak power density ( Figure 7 ) and better battery stability ( Figure 8 ). Thus, the material of Example 1 is 2 Saturated 0.5MH 2 SO 4 Excellent electrocatalytic ORR performance was demonstrated in both solution and actual hydrogen fuel cell test systems.
[0062] Example 2
[0063] First, 1.5 g of dibenzyl disulfide was weighed and dispersed into 20 mL of graphene oxide dispersion (2 mg / mL), and the dibenzyl disulfide was completely dissolved by ultrasonication for 30 min. Then, the dispersion after dissolving dibenzyl disulfide was placed in a polytetrafluoroethylene reactor, reacted at 160 ° C for 15 h, filtered, washed, and dried to obtain sulfur-doped graphene nanosheets (SG). 2 g of 2-methylimidazole, 0.3 g of zinc nitrate hexahydrate, and 0.01 g of CTAB were dissolved in 50 mL of deionized water, stirred and dissolved, and then allowed to stand for 5 h, centrifuged, washed, and dried to obtain ZIF-8 nanocubes. SG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20 min, and centrifuged and washed 3 times, each time for 5 min, to obtain sulfur-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h, and after drying, the sulfur-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace. After argon was introduced for 30 min, it was heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, sulfur- and nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / SG@HNCs). 2 Saturated 0.5MH 2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0064] Example 3
[0065] First, 1.5g of urea was weighed and dispersed into 50mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 15h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace, argon was introduced for 30 min, and then heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0066] Example 4
[0067] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 200℃ for 15h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace, argon was introduced for 30 min, and then heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0068] Example 5
[0069] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 15h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.7g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace, argon was introduced for 30 min, and then heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0070] Example 6
[0071] First, 1.5 g of urea was weighed and dispersed into 20 mL of graphene oxide dispersion (2 mg / mL), and the urea was completely dissolved by ultrasonication for 30 min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160 ° C for 24 h, filtered, washed, and dried to obtain nitrogen-doped graphene nanosheets (NG). 2 g of 2-methylimidazole, 0.3 g of zinc nitrate hexahydrate, and 0.01 g of CTAC were dissolved in 50 mL of deionized water, stirred and dissolved, and then allowed to stand for 5 h, centrifuged, washed, and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20 min, and centrifuged and washed 3 times, each time for 5 min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace, argon was introduced for 30 min, and then heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0072] Example 7
[0073] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 24h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 10h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L nickel acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace, argon was introduced for 30 min, and then heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0074] Example 8
[0075] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 24h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 0.5 mol / L ferric acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace. After argon was introduced for 30 min, it was heated to 800 °C at a heating rate of 5 °C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0076] Example 9
[0077] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 24h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a 3 mol / L nickel acetate solution for 12 h, and after drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace. After passing Ar gas for 30 min, it was heated to 800 ° C at a heating rate of 5 ° C / min and kept warm for 4 h to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0078] Example 10
[0079] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 24h, filtered, washed and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole, 0.3g of zinc nitrate hexahydrate and 0.01g of CTAB were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a nickel acetate solution with a concentration of 3 mol / L for 12 hours. After drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, placed in a tube furnace, and after passing Ar gas for 30 minutes, it was heated to 950°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain the final product, nitrogen-doped hollow multi-level porous carbon nanocage electrocatalyst (NC / G@HNCs). 2 Saturated 0.5MH 2 SO 4 It exhibits excellent electrocatalytic oxygen reduction reaction performance in solution.
[0080] Comparative Example 1
[0081] First, 20 mL of graphene oxide dispersion (2 mg / mL) was placed in a polytetrafluoroethylene reactor, reacted at 160 ° C for 15 h, filtered, washed, and dried to obtain graphene nanosheets (r-GO) without heteroatom doping. 2 g of 2-methylimidazole, 0.3 g of zinc nitrate hexahydrate, and 0.01 g of CTAB were dissolved in 50 mL of deionized water, stirred and dissolved, and then allowed to stand for 5 h, centrifuged, washed, and dried to obtain ZIF-8 nanocubes. r-GO and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20 min, and centrifuged and washed 3 times, each time for 5 min, to obtain undoped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a nickel acetate solution with a concentration of 0.5 mol / L for 12 hours, and after drying, the graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, and then placed in a tube furnace, argon was introduced for 30 minutes, and then heated to 800°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain the final product, a hollow multi-level porous carbon nanocage electrocatalyst (HNCs). 2 Saturated 0.5MH 2 SO4 The electrocatalytic performance of oxygen reduction in solution is inferior to that of heteroatom-doped carbon nanocage catalysts (e.g. NC / G@HNCs). Fig. 9 ). The main reason is that in the absence of heteroatom doping, it is impossible to induce electronic coupling and intermolecular electron transfer through heterogeneous interfaces doped with heteroatoms, which is not conducive to the generation of a large number of catalytic active sites, thus resulting in poor catalytic activity.
[0082] Comparative Example 2
[0083] First, 1.5g of urea was weighed and dispersed into 20mL of graphene oxide dispersion (2mg / mL), and the urea was completely dissolved by ultrasonication for 30min. Then, the dispersion after dissolving urea was placed in a polytetrafluoroethylene reactor, reacted at 160℃ for 15h, filtered, washed, and dried to obtain nitrogen-doped graphene nanosheets (NG). 2g of 2-methylimidazole and 0.3g of zinc nitrate hexahydrate were dissolved in 50mL of deionized water, stirred and dissolved, and then allowed to stand for 5h, centrifuged, washed, and dried to obtain ZIF-8 nanocubes. NG and ZIF-8 were uniformly mixed in a mass ratio of 1:1, stirred for 20min, and centrifuged and washed 3 times, each time for 5min, to obtain nitrogen-doped graphene / ZIF-8 nanohybrid materials. The copper foam was immersed in a nickel acetate solution with a concentration of 0.5 mol / L for 12 hours. After drying, the nitrogen-doped graphene / ZIF-8 nanohybrid material was attached to the surface of the copper foam, placed in a tubular furnace, and after passing argon for 30 minutes, it was heated to 800°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain the final product, nitrogen-doped nanocarbon electrocatalyst (N-CG). Since the cationic surfactant CTAB was not used in the synthesis of ZIF-8, it was impossible to obtain ZIF-8 cubes with strong positive charge on the surface, resulting in the random mixing of nitrogen-doped graphene and ZIF-8, and no graphene-coated ZIF-8 (core-shell) structure ( Fig.10 ), failed to obtain a heterojunction structure between the two. 2 Saturated 0.5MH 2 SO 4 The electrocatalytic performance of oxygen reduction in solution is inferior to that of heteroatom-doped carbon nanocage catalysts (e.g. NC / G@HNCs). Fig. 9 ).
Claims
1. A hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst, characterized in that: The electrocatalyst has a hollow multi-level porous carbon nanocage structure formed by hybridization of non-metallic heteroatom-doped graphene nanosheets and a zeolite imidazole metal covalent organic framework with a surface modified positive charge; the non-metallic heteroatom-doped graphene nanosheets and the zeolite imidazole metal covalent organic framework are in close contact to form a nano heterojunction; the non-metallic heteroatom is at least one of boron, nitrogen, sulfur, phosphorus and fluorine; the mass percentage of the non-metallic heteroatom-doped graphene nanosheets in the hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst is 25-50%.
2. The hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst according to claim 1, characterized in that: The zeolite imidazole metal covalent organic framework is at least one of ZIF-8, ZIF-20, ZIF-90, ZIF-4, and ZIF-7.
3. The hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst according to claim 1, characterized in that: The mass percentage of heteroatoms in the non-metallic heteroatom-doped graphene nanosheets is 3-10%.
4. The hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst according to claim 1, characterized in that: The size of the carbon nanocage is 100-300 nm.
5. The hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst according to claim 1, characterized in that: The electrocatalyst has a hierarchical porous structure in which micropores, mesopores and macropores are interconnected and coexist, and the pore size ranges from 0.6 to 100 nm.
6. The method for preparing the hollow multi-level porous carbon nano cage oxygen reduction reaction electrocatalyst according to any one of claims 1 to 5, characterized in that: The preparation method uses heteroatom-doped graphene and zeolite imidazole metal covalent organic framework cubes with positive charges on the surface as building blocks, forms a carbon nano-hybrid material through non-covalent interaction between the two, and uses small molecule hot air flow generated by the decomposition of acetate to swell the micropores in the zeolite imidazole metal covalent organic framework, and finally forms a carbon nano-cage oxygen reduction reaction electrocatalyst with a multi-level pore structure with an internal cavity.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: 1) Synthesis of non-metallic heteroatom-doped graphene nanosheets using a hydrothermal method; 2) Preparation of zeolitic imidazole metal covalent organic framework nanocubes with surface modification of positive charges; 3) Electrostatic self-assembly of non-metallic heteroatom-doped graphene nanosheets and surface-modified positively charged zeolite imidazole metal covalent organic framework nanocubes to obtain non-metallic heteroatom-doped graphene / zeolite imidazole metal covalent organic framework hybrid materials; 4) Placing the non-metallic heteroatom doped graphene / zeolite imidazole metal covalent organic framework hybrid material on the surface of copper foam with acetate groups, and pyrolyzing it at high temperature in an inert atmosphere to obtain the hollow multi-level porous carbon nanocage oxygen reduction reaction electrocatalyst.
8. The preparation method according to claim 7, characterized in that: In step 1), the synthesis of non-metallic heteroatom-doped graphene nanosheets by hydrothermal method includes: ultrasonically dispersing heteroatom dopants into an aqueous dispersion of graphene oxide, and obtaining heteroatom-doped graphene nanosheets by hydrothermal reaction.
9. The preparation method according to claim 8, characterized in that The temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 12-24 h.
10. The preparation method according to claim 8, characterized in that: The mass ratio of the heteroatom dopant to graphene oxide is (1-5): (0.1-0.5).
11. The preparation method according to claim 8, characterized in that: The heteroatom dopant is at least one of boric acid, melamine, urea, dibenzyl disulfide, triphenylphosphine, thiourea and ammonium fluoride.
12. The preparation method according to claim 7, characterized in that: In step 2), the preparation of the surface-modified positively charged zeolite imidazole metal covalent organic framework nanocubes comprises: uniformly mixing 2-methylimidazole, zinc nitrate hexahydrate and a cationic surfactant, stirring and standing to obtain the surface-modified positively charged zeolite imidazole metal covalent organic framework nanocubes.
13. The preparation method according to claim 12, characterized in that: The mass ratio of the 2-methylimidazole, zinc nitrate hexahydrate and cationic surfactant is (1-10): (0.1-1): (0.01-0.06).
14. The preparation method according to claim 12, characterized in that: The cationic surfactant is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and cetyldimethylbenzylammonium chloride.
15. The preparation method according to claim 7, characterized in that: In step 4), the pyrolysis temperature is 700-1000°C and the pyrolysis time is 3-5 h.
Citation Information
Patent Citations
Nitrogen-doped three-dimensional nano porous carbon / porous graphene composite material and preparation method thereof
CN106058196A
KR20190009541A